Identifying gaps and providing recommendations to address shortcomings in the investigation of acne sequelae by the Personalising Acne: Consensus of Experts panelCapsule Summary - Alison Layton, MB, ChB; Andrew Alexis, MD, MPH; Hilary Baldwin, MD; Stefan Beissert, MD; Vincenzo Bettoli, MD; James Del Rosso, DO; Brigitte Dréno, MD, PhD; Linda Stein Gold, MD; Julie Harper, MD; Charles Lynde, MD; Diane Thiboutot, MD; Jonathan Weiss, MD; et al. (Elsevier, 2021)
Background: The physical sequelae of acne include erythema, hyperpigmentation, and scarring, which are highly burdensome for patients. Early, effective treatment can potentially limit and prevent sequelae development, but there is a need for guidance for and evidence of prevention-oriented management to improve patient outcomes. Objective: To identify unmet needs of acne sequelae and generate expert recommendations to address gaps in clinical guidance. Methods: The Personalizing Acne: Consensus of Experts panel of 13 dermatologists used a modified Delphi approach to achieve a consensus on the clinical aspects of acne sequelae. A consensus was defined as ≥75% of the dermatologists voting "agree" or "strongly agree." All voting was electronic and blinded. Results: The panel identified gaps in current guidance and made recommendations related to acne sequelae. These included identification and classification of sequelae, pertinent points to consider for patient consultations, and management aimed at reducing the development of sequelae. Limitations: The recommendations are based on expert opinion and made in the absence of high-quality evidence. Conclusions: The identified gaps should help inform future research and guideline development for acne sequelae. The consensus-based recommendations should also support the process of consultations throughout the patient journey, helping to reduce the development and burden of acne sequelae through improved risk factor recognition, early discussion, and appropriate management.